PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA DENGAN MODEL PROBLEM SOLVING - SRI UTAMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The low science learning outcomes are caused by the dominance of memorization skills rather than the ability to process their own understanding of a material. In addition, the low learning motivation of students in science with an indication of student activity during the learning process is an important thing that must be evaluated by the teacher. The use of learning models is prioritized to stimulate the active role of students in the learning process. Problem solving is a learning model to construct their own knowledge, increase learning activity, build critical, creative, and communicative attitudes. This study aims to determine the activities and learning outcomes of students after implementing problem solving. This type of research is classroom action research which consists of two cycles. The subjects of this research are class VIIA students of MTsN Tlasih Sidoarjo. Data collection techniques used two kinds, namely observation and tests. Based on the results of the study, it was concluded that the learning activities of class VIIA MTsN Tlasih Sidoarjo students increased by 12.27%, the average science test scores were 18.44, and learning completeness was 50%. ABSTRAKMasih rendahnya hasil belajar IPA disebabkan oleh masih dominannya skill menghafal daripada skill memproses sendiri pemahaman suatu materi. Selain itu rendahnya motivasi belajar siswa pada IPA dengan indikasi aktivitas siswa pada saat proses pembelajaran merupakan hal penting yang harus dievaluasi guru. Penggunaan model pembelajaran sangat diutamakan untuk menstimulus peran aktif siswa dalam proses pembelajaran. Problem solving merupakan model pembelajaran mengkonstruksi pengetahuannya sendiri, meningkatkan keaktifan belajar, membangun sikap kritis, kreatif, dan komunikatif. Penelitian ini bertujuan untuk mengetahui aktivitas dan hasil belajar siswa setelah menerapkan problem solving. Jenis penelitian ini merupakan penelitian tindakan kelas yang terdiri dua siklus. Subyek penelitian ini yatu siswa kelas VIIA MTsN Tlasih Sidoarjo. Teknik pengumpulan data menggunakan dua macam yaitu observasi dan tes. Berdasarkan hasil penelitian, disimpulkan bahwa aktivitas belajar siswa kelas VIIA MTsN Tlasih Sidoarjo mengalami peningkatan sebesar 12,27%, rata-rata nilai tes IPA sebesar 18,44, dan ketuntasan belajar sebesar 50%.